Inborn errors of immunity in mainland China: the past, present and future - Huawei Mao; Mengyue Deng (BMJ Publishing Group, 2023)
Inborn errors of immunity (IEI), also known as primary immunodeficiency diseases, comprise a group of rare genetic disorders that affect the development or/and function of the immune system. These disorders predispose individuals to recurrent infections, autoimmunity, cancer and immune dysregulations. The field of IEI diagnosis and treatment in mainland China has made significant strides in recent years due to advances in genome sequencing, genetics, immunology and treatment strategies. However, the accessibility and affordability of diagnostic facilities and precision treatments remain variable among different regions. With the increasing government emphasis on rare disease prevention, diagnosis, and treatment, the field of IEI is expected to progress further in mainland China. Herein, we reviewed the development and current state of IEI in mainland China, highlighting the achievements made, as well as opportunities and challenges that lie ahead.